Uncomfortable otherness: a sociological reflection - Cartagena Núñez, Catalina (2021)
This article reflects on some of the mechanisms at work in the social construction of Otherness from a sociological perspective. For this, an approximation is made of the processes that produce social classifications and we deep dive into three separate markers of identification and differentiation: social class, race and sex-gender. The consequences of the classification patterns that divide the world into dichotomous opposites in social processes are analyzed, highlighting the relationships between these systems and the dynamics of inequality and asymmetry between groups and social beings.